Cryptosporidium and Giardia in cats and dogs: What is the real zoonotic risk? - Barbosa, Amanda D.; Egan, Siobhon; Feng, Yaoyu; Xiao, Lihua; Ryan, Una (Current research in parasitology & vector-borne diseases, 2023)
Due to the close bond between humans and companion animals, a thorough understanding of the diversity of species and assemblages in cats and dogs is essential to determine the potential zoonotic risks. Analysis of molecular studies shows that and are the main species infecting cats and dogs, respectively. These species are largely host-specific, as despite intense association with humans, prevalence of and in humans is low and predominantly in immunocompromised individuals and low-income countries. There have been reports of in cats and dogs and two reports of in dogs. In most studies conducted to date, however, the prevalence of zoonotic species was low and may be associated with coprophagy and or/spillback, but this remains to be determined. Results of subtyping studies suggest that for and , some zoonotic transmission may occur but host-adapted subtypes also exist. assemblages C and D are commonly reported in dogs, with assemblages F and A most common in cats. Assemblages C, D and F are largely host-specific as there are only a handful of reports of them in humans. Reports of assemblage A and B in cats and dogs may be due to coprophagy or spillback from owners. Despite the extent of pet ownership and the close contact between humans and companion animals worldwide, the overall risk of zoonotic transmission from cats and dogs to humans is uncertain but thought to be low due to , and assemblages C, D and F being predominantly host-specific, the relatively low prevalence of (and ) in cats and dogs (which may be due to mechanical carriage), and low oo/cyst shedding. Carefully designed epidemiological studies of cats and dogs and their owners using subtyping tools are essential to better quantify the extent of spillover and spillback of and between pets and their owners.